Automated Comparison of Structural Durability Analyses of Automotive Structures. (2015) - Lohse, Sebastian; Bruder, Thomas; Wong, Keng-Jin
Abstract: A software environment designed with respect to fast analyses and ease-of-use, allows to speed up the development process using an automated comparison of experimental and numerical fatigue analysis. The automated process prevents errors, is significantly faster and allows the validation of the FEA result. To demonstrate the user benefit a battery mounting assembly in a passenger car was chosen. Using the software environment, differences between the numerical analysis and the test were evaluated. While a simple comparison of the fatigue analysis results suggested a good fit, the detailed report led to a reevaluation of the finite element model.